The ethics of pandemic preparedness revisited - autonomy, quarantine, transferability and trust. (30th September 2020) - Schröder-Bäck, P; Schloemer, T; Martakis, K; Brall, C
Abstract: Background: The outbreak of SARS in 2002 lead to a public health ethics discourse. The crisis management of that time was ethically analysed and lessons to be learned discussed. Scholarship and WHO, among others, developed an ethics of pandemic preparedness. The current "corona crisis" also faces us with ethical challenges. This presentation is comparing the two crises from an ethical point of view and a focus on Europe. Methods: An ethics framework for pandemic preparedness (Schröder et al. 2006 and Schröder-Bäck 2014) is used to make a synopsis of ethical issues. Ethical aspects of 2002 and 2020 that were discussed in the literature and in the media are compared. For 2020, the focus is on interventions in Italy, Germany, Switzerland, and the Netherlands. Results: Topics that emerged from the 2002 crisis were, among others, revolving around aspects of stigmatisation and fair distribution of scarce resources (esp. vaccines, antivirals). Currently, most urgent and ethically challenging aspects relate to social distancing vs. autonomy: Isolation and quarantine are handled differently across Europe and the EU. Questions of transferability of such interventions prevail. Contexts vary vertically over time (2002 vs. 2020) and horizontally (e.g. between Italy and Germany at the same time). Furthermore, trust in authorities, media and health information is a key issue. Conclusions: Ethical aspects are key for good pandemic preparedness and management. The context of the crises between 2002 and 2020 has slightly changed, also based on "lessons learned" from 2002. This has implications on ethical issues that are being discussed. New lessons will have to be learned from the 2020 crisis. Key messages: Pandemic preparedness and outbreak management entail many ethical tensions that need to be addressed. Currently, questions of trust and transferability are key to the crisis management, further ethical issues could still emerge.